Reduced mitochondrial DNA content in lymphocytes is associated with insulin resistance and inflammation in patients with impaired fasting glucose - Abu Bakar, Mohamad Hafizi; Hairunisa, Nany; Huri, Hasniza Zaman (Springer, 2018)
Altered mitochondrial DNA (mtDNA) is the most common denominator to numerous metabolic diseases. The present study sought to investigate the correlation between mtDNA content in lymphocytes and associated clinical risk factors for impaired fasting glucose (IFG). We included 23 healthy control and 42 IFG participants in this cross-sectional study. The measurements of mtDNA content in lymphocytes and pro-inflammatory markers derived from both normal and diseased individuals were quantified. Spearman partial correlation and multivariate statistical analyses were employed to evaluate the association between mtDNA content and other metabolic covariates in IFG. Reduced mtDNA content was observed in the IFG group with microvascular complications than those without complications. The IFG patients with lowest median of mtDNA content had considerably elevated hyperglycemia, insulin resistance and inflammation. The adjusted partial correlation analysis showed that mtDNA content was positively correlated with HDL-cholesterol and IL-10 (P < 0.005 for all). Further, multiple linear regression analyses verified that reduced mtDNA content in lymphocytes was independently associated with HOMA-IR (β = 0.027, P = 0.003), HbA1c (β = 0.652, P = 0.002), HDL-cholesterol (β = − 1.056, P = 0.021), IL-6 (β = 0.423, P = 0.002), IL-10 (β = − 1.234, P = 0.043) and TNF-α (β = 0.542, P < 0.001) after adjustment for confounding factors. Our data show that reduced mtDNA content in lymphocytes was associated with insulin resistance and inflammation in individuals with IFG.